Inside Back Cover: Volume 2 Issue 3. (30th September 2021) - Yao, Ze‐Fan; Li, Qi‐Yi; Wu, Hao‐Tian; Ding, Yi‐Fan; Wang, Zi‐Yuan; Lu, Yang; Wang, Jie‐Yu; Pei, Jian
Abstract : Inside back cover image : Crystal structure of π‐conjugated small molecules and polymers is fundamentally critical to understand the multilevel microstructures. However, determining the crystal structure of conjugated polymers remains a significant challenge. Jian Pei and coworkers build the possible crystal structures of eight typical conjugated polymers, covering several widely used molecular segments in organic optoelectronics. These crystal structures are modeled by combining synchrotron X‐ray diffractions and molecular simulations, which compose a crystal structure database of conjugated polymers, providing a new platform to predict the possible packing structures and charge transport properties of related polymers. Such crystal structure database of conjugated polymers aims to accelerate the intelligent design of high‐performance conjugated polymers. (DOI: https://doi.org/10.1002/smm2.1053 )